A 27 day persistence model of near‐Earth solar wind conditions: A long lead‐time forecast and a benchmark for dynamical models. Issue 5 (2nd May 2013) - Owens, M. J.; Challen, R.; Methven, J.; Henley, E.; Jackson, D. R.
Abstract : Geomagnetic activity has long been known to exhibit approximately 27 day periodicity, resulting from solar wind structures repeating each solar rotation. Thus a very simple near‐Earth solar wind forecast is 27 day persistence, wherein the near‐Earth solar wind conditions today are assumed to be identical to those 27 days previously. Effective use of such a persistence model as a forecast tool, however, requires the performance and uncertainty to be fully characterized. The first half of this study determines which solar wind parameters can be reliably forecast by persistence and how the forecast skill varies with the solar cycle. The second half of the study shows how persistence can provide a useful benchmark for more sophisticated forecast schemes, namely physics‐based numerical models. Point‐by‐point assessment methods, such as correlation and mean‐square error, find persistence skill comparable to numerical models during solar minimum, despite the 27 day lead time of persistence forecasts, versus 2–5 days for numerical schemes. At solar maximum, however, the dynamic nature of the corona means 27 day persistence is no longer a good approximation and skill scores suggest persistence is out‐performed by numerical models for almost all solar wind parameters. But point‐by‐point assessment techniques are not always a reliable indicator of usefulness as a forecast tool. An event‐based assessment method, which focusses key solar wind structures, finds persistence to be the most valuable forecast throughout the solar cycle. This reiterates the fact that the means of assessing the "best" forecast model must be specifically tailored to its intended use. Key Points: 27‐day persistence model provides a useful solar wind forecast Persistence skill is equal to mhd models at solar min, but lower at solar max Persistence model provides a benchmark for dynamical models